2020
DOI: 10.35975/apic.v24i6.1209
|View full text |Cite
|
Sign up to set email alerts
|

A way to improve neuro regional analgesia: what adjuvant is the best? A narrative review.

Abstract: Introduction. The aim of this review was to systematize known facts about the effects of adjuvants to local anesthetics in order to determine adjuvant with the best effect among all others. More precisely the time of action onset, depth of the effect, duration of the block and some additional effects such as “marker of intravascular injection”, safety and toxicity profile, along with the adjuvant, which have all these properties in a sufficient degree. Materials and methods. We searched for information i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
2
3
0
Order By: Relevance
“…The results of our study confirmed that inadequate perioperative analgesia and neglecting the principles of multimodal analgesia could result in the development of chronic pain syndrome [28], [29], [30], [31].…”
Section: Discussionsupporting
confidence: 76%
“…The results of our study confirmed that inadequate perioperative analgesia and neglecting the principles of multimodal analgesia could result in the development of chronic pain syndrome [28], [29], [30], [31].…”
Section: Discussionsupporting
confidence: 76%
“…The results of our study confirmed that inadequate perioperative analgesia and neglecting the principles of multimodal analgesia could result in the development of chronic pain syndrome [6,7,38]. According to QoL questionnaires, in patients with pain in the early postoperative period, the indicators on some scales reduced significantly as compared to children without pain.…”
Section: Discussionsupporting
confidence: 71%
“…As with every advanced development in science and technology, AI and machine learning as a field of study have received both significant support and criticism regarding the scientific and ethical aspects and data protection issues. [25][26][27] Criticism was caused by the complexity of technical support for controlling big data, which is the basis for the application of AI technology. Studies have been conducted on this issue.…”
Section: Discussionmentioning
confidence: 99%